Prohibited elements in Islamic financial transactions: a comprehensive review - Saiti, Buerhan; Abdullah, Adam (IIUM, 2016)
This paper analyzes prohibited elements in transactions from a shari’ah perspective, since it is obligatory on the individual (fardhu ‘ayn) to understand the Islamic law of transactions (fiqh mu’amalat). Islam is not only a religion, but also a complete way of life. Islam has clearly forbidden all business transactions that lead to exploitation and injustice in any form to any of the parties of a contract. Islam requires that all financial and business transactions be based on transparency, accuracy, and disclosure of all material information so that no one party takes advantage of other parties. There is wisdom (hikmah) behind every prohibited transaction and in order to practice business and banking activities that are genuinely shari’ahcompliant, it is important to understand the prohibited elements in Islamic law. Accordingly, prohibited elements such as riba, gharar, qimar, maysir, fraud and coercion are discussed, as well as, the importance of the legality of the subject matter. Sahih, fasid, batil contracts and extrinsic conditions are covered in respect to different schools of thought